Ethnographier un établissement psychiatrique en qualité d’élève directrice d’hôpital - Audrey Higelin-Cruz (Terrains/Théories)
This article is based on ethnographic fieldwork that took place over an eight-week period in a public mental health institution, which dovetailed with the observation exercises that were part of the researcher’s training as a hospital manager. This work-placement offered the opportunity for targeted research, focusing on one of France’s largest hospitals in terms of budget and caseload, practicing general psychiatry, child and adolescent psychiatry, as well as psychiatry for the elderly. This article seeks to examine the opportunities and constraints of various specific ways of carrying out enquiries, and the kinds of results that they generate. The researcher, a sociologist who is becoming progressively integrated into the hospital sector, questions thereby the advantages and limits of this "dual status" (sociologist + insider), before discussing how the specific conditions of the enquiry made it possible to re-evaluate the role of the concept of the "total institution" on the profession.